2020
DOI: 10.1016/j.omtm.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermally Induced Configuration Changes on rAAV Genome’s Enzymatic Accessibility

Abstract: Physical titers for recombinant adeno-associated viral (rAAV) vectors are measured by quantifying viral genomes. It is generally perceived that AAV virions disassemble and release DNA upon thermal treatment. Here, we present data on enzymatic accessibility of rAAV genomes when AAV virions were subjected to thermal treatment. For rAAV vectors with a normal genome size (≤4.7 kb), thermal treatment at 75°C–99°C allowed only ∼10% of genomes to be detectable by quantitative real-time PCR. In contrast, greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A number of previous studies have reported on temperature-induced changes in AAV vectors. [69][70][71][72] A more detailed accounting of the CDMS measurements will be reported elsewhere. We mention these results here because we use the masses from the heat-treated samples below.…”
Section: Resultsmentioning
confidence: 99%
“…A number of previous studies have reported on temperature-induced changes in AAV vectors. [69][70][71][72] A more detailed accounting of the CDMS measurements will be reported elsewhere. We mention these results here because we use the masses from the heat-treated samples below.…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, the TIANamp Virus DNA/RNA Kit (Tiangen, Beijing, China) was employed for extracting total cellular DNA as described in the manufacturer's guidance. qPCR was conducted with the AceQ qPCR SYBR Green Master Mix kit (SYBR Green I, Vazyme Biotechnology, Nanjing, China) using transgene-specific primers to measure the infection efficiency of rAAV as described previously [ 20 ]. For internalization assays, cells were infected for 1 h at 4 °C and cultured for 1 h at 37 °C with 5% CO 2 , followed by trypsin treatment to remove those non-internalized surface-bound virions.…”
Section: Methodsmentioning
confidence: 99%
“…The copurified DNA is, in most of the cases, removed by a Benzonase or DNase I treatment during downstream processing. , These species should be monitored carefully due to their potential genotoxicity . Another source of external DNA can be encapsidated DNA, which can be ejected from the capsid when samples are stressed. , Next to the external, also internal DNA can contain selection markers but also fragments or truncated forms of the intended genome. All of these species are potentially immunogenic and/or genotoxic for patients . For this reason, profound characterization of the rAAV genome is of the utmost importance to ensure a safe and effective product.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Another source of external DNA can be encapsidated DNA, which can be ejected from the capsid when samples are stressed. 18 , 19 Next to the external, also internal DNA can contain selection markers but also fragments or truncated forms of the intended genome. 20 23 All of these species are potentially immunogenic and/or genotoxic for patients.…”
Section: Introductionmentioning
confidence: 99%